An annotated bibliography of presentation of information in aircraft cockpits - Fox, J. G.; Andrew, I. D. C.; Ferguson, I. (College of Aeronautics, 1965)
INTRODUCTION In the preparation of, this bibliography only data which has been published after 1940 has been considered. The choice of this 'cut-off' point seemed, reasonable on two counts: it begins a period when cockpit displays become more varied and steadily become more complex so that the pilot's normal capacities increasingly become a limiting factor in the efficiency of the system: and it was in the early 'forties' that man's capacities first began to be related explicitly to equipment design. It would however have been presumptious to consider that no work before 1940 had any relevance; that some current principles could not be supported or rejected on the basis of pre-war research or practice. But it is unlikely that the pursuit of earlier work would have added anything to the information given by Nickles (1958) in A. History of Aircraft Cockpit Instrumentation1221:19LE. This admirable review is concerned primarily in showing how each instrument evolved and its purpose, how information was displayed in the cockpit and the mechanical principles employed. But it also considers the empirical solution to implicit ergonomic problems in this area, tracing the manner in which instruments were combined, simplified and arranged for better presentation. In some measure it warns against the presumption of ignoring early data for it points out that the 'recently' evolved principle of grouping instruments in horizontal or vertical arrays to ease the visual task of the pilot was suggested by Doolittle in his 'fog flying' experiments in 1929 … [cont.].